Self-Repair Practices in Pharmacist-Patient Interaction and their Role in Preventing Misunderstanding and Maintaining Medication Safety - Delli, Rami Maher; Kaur, Jagdish; Lai, Siew Mei Pauline; Dumanig, Francisco Perlas (Respectus Philologicus, 2022)
Effective communication between pharmacists and patients can prevent medication errors as it enhances patients’ understanding of their medication and increases their adherence. As misunderstanding may occur in any type of interaction and lead to communication breakdown, repair practices that speakers adopt to enhance understanding in interaction are an especially important area of research in Conversation Analysis (CA). As such, this study aims to identify and explain the self-repair practices used by pharmacists to increase patient understanding in spoken interaction. The study was conducted at the University of Malaya Medical Centre from November to December 2014. Four pharmacists and 27 patients were recruited to participate in an intervention study. A detailed sequential analysis of interaction data revealed the pharmacists’ use of replacement, clarification, verbatim repeat, and repetition with an elaboration designed to increase the clarity and accuracy of the intended message and improve patient understanding. Self-repair practices may have an essential role in increasing medication safety in the healthcare setting.